Longitudinal roll patterns of Marangoni instability in an easily volatile sessile droplet evaporating at constant contact angle mode. (May 2019) - Zhu, Ji-Long; Shi, Wan-Yuan
Highlights: Spoke-like patterns with several rolls uniformly distributed in azimuthal direction were observed in droplets. Each roll straightly extends to the center of droplet and its axis is parallel to radial axis. Patterns are longitudinal rolls driven by inclined temperature gradient. Abstract: Marangoni instabilities in an easily volatile sessile droplet of n-hexane evaporating at constant contact angle mode were investigated through a series of experiments. Once the droplet is deposited onto the substrate, a kind of spoke-like pattern with several rolls uniformly distributed in azimuthal direction is generated soon in the droplet. Different from the Bénard-Marangoni cell and the hydrothermal wave, each roll straightly extends to the center of the droplet and the axis of the roll is parallel to the radial axis of the droplet. They do not propagate neither in radial direction nor in azimuthal direction. With the receding of the wetting radius, the neighbor two rolls merge into one roll and a few of new rolls quickly generate in random positions, and the roll number gradually decreases until the vanishment of droplet. During evaporation, they sustain a quasi-steady state. We believe that these rolls belong to the longitudinal rolls driven by the inclined temperature gradient in droplet. The influences of the substrate temperature, the ambient temperature and the contact angle on the behavior of the longitudinal rolls are analyzed.